Music in Nigerian education - Okafor, Richard C. (International Library of African Music, 1992)
In the traditional Nigerian society music was an integral part of education. A musician was often expected to practice other areas of the arts and occupations. There were musical families with long traditions of music making. There were instrument makers who were also expected to practice other areas of occupation. Training in music often involved a long period of apprenticeship during which the trainee learned other aspects of the art.
Keywords: Education; African Music; Nigeria